Application of Activated Carbon Derived from Typha domingensis in Industrial Wastewater Treatment - Jabir Danyaya Aliyu; Ibrahim Abubakar; Zayyanu Abdullahi; Sadiq Musa (Journal of Bioresources and Environmental Sciences, 2026)
Water pollution due to discharge of industrial wastes into aquatic environment remains a major challenge associated with adverse health effects and environmental destruction worldwide. The activated carbon was produced from the plant biosorbent using potassium hydroxide activator method. The activated carbon produced was characterized by surface characteristics and Fourier Transform Infrared (FTIR) spectroscopic technique. The levels of heavy metals in the treated and untreated industrial wastewater sample were determined by atomic absorption spectroscopic (AAS) technique. Batch adsorption study was conducted using the American Public Health Association (APHA) method. The mechanism of heavy metals adsorption capacity of the plant-derived activated carbon was evaluated using Freundlich isotherm and Langmuir isotherm models. The result showed that the plant-derived activated carbon derived exhibited significant (p < 0.05) value of surface area (570.33 m2/g), pore volume (2.56 g/cm3), pH (6.46), conductivity (64.03 µS/cm), moisture content (20.86 %), and ash content (7.53 %) coupled with low value of porosity (0.82 %), bulk density (0.53 g/cm3), apparent density (0.32 g/cm3), and real density (1.91 g/cm3).. The FT-IR spectrum of the activated carbon displayed various band peaks at wavenumber ranged 3350 – 801 cm−1 indicating stretching of C–H, C=O, C–C C−O, and O−H. The untreated wastewater sample demonstrated high significant (p < 0.05) amount of cadmium (0.23 mg/L), cobalt (0.83 mg/L), lead (3.02 mg/L), manganese (1.47 mg/L), nickel (0.62 mg/L), and chromium (0.60 mg/L). The plant-derived activated carbon exhibited high significant (p < 0.05) percentage efficiency for removal of cadmium (95.55 %), cobalt (96.48 %), lead (97.16 %), manganese (99.25 %), nickel (96.09 %), and chromium (96.88 %) from the industrial wastewater sample. The results of this study showed that the regression coefficient (R²) values of cadmium, cobalt, lead, manganese, nickel, and chromium for the Langmuir isotherm are higher than that demonstrated by the metals for the Freundlich isotherm model. The experimental equilibrium data for cadmium, cobalt, lead, manganese, nickel, and chromium were best fitted to the Langmuir isotherm model than the Freundlich isotherm model. The activated carbon derived from the roots of Typha domingensis demonstrated high adsorption capacity for removal of cadmium, cobalt, lead, manganese, nickel, and chromium from the industrial wastewater.